Geoelectric Assessment of Regolith Aquifer and Its Vulnerability, in a Typical Basement Complex Terrain, Southwestern Nigeria - Igboama, Wilfred N.; Aroyehun, Morufu T.; Hammed, Olaide S. (Malaysian Journal of Science, 2025)
Assessment of groundwater potential cum regolith aquifer protective strength was carried out using the electrical resistivity method at Ikole Ekiti, Southwestern Nigeria, to assess its viability and susceptibility. The Vertical Electrical Sounding (VES) technique using the Schlumberger array was adopted. The acquired data was partially curve-matched, forward-modelled, and iterated using WinResist version 1.0 software. Charts, para sections, tables, and maps were generated from the results obtained to aid interpretations. The KH curve type, which indicates good protective capacity, is more predominant in the study area than other curve types. Parasections showed four (4) geoelectric layers, i.e., topsoil, upper saprolite, lower saprolite, and sap rock. A weathered layer is the principal aquifer unit identified in the area; it is appreciably thick, and the basement is fresh. The thickness of regolith ranges from 2 to 56 m, with an appreciable thickness that can sustain moderate groundwater yield in the southern region of Ikole. The layer above the regolith aquifer has an average thickness slightly below 20 m; therefore, areas without lateritic cover will be prone to pollution. The strength of the regolith aquifer was assessed by employing longitudinal conductance (LC) and Geoelectric Layer Susceptibility Index (GLSI) ratings. The inherent weakness of the LC rating (not accounting for the lateritic nature of soil) was complemented by the GLSI rating. The southern region of the study area where groundwater is feasible is evaluated to have moderate protective capacity. Therefore, sources of pollution, such as septic tanks and dump sites, should be located far away from the area.